Metabolic implications for predatory and parasitic bacterial lineages in activated sludge wastewater treatment systems - Kyohei Kuroda; Shun Tomita; Hazuki Kurashita; Masashi Hatamoto; Takashi Yamaguchi; Tomoyuki Hori; Tomo Aoyagi; Yuya Sato; Tomohiro Inaba; Hiroshi Habe; Hideyuki Tamaki; Yoshihisa Hagihara; et al. (Water Research X, 2023)
Deciphering unclear microbial interactions is key to improving biological wastewater treatment processes. Microbial predation and parasitism in wastewater treatment ecosystems are unexplored survival strategies that have long been known and have recently attracted attention because these interspecies interactions may contribute to the reduction of excess sludge. Here, microbial community profiling of 600 activated sludge samples taken from six industrial and one municipal wastewater treatment processes (WWTPs) was conducted. To identify the shared lineages in the WWTPs, the shared microbial constituents were defined as the family level taxa that had ≥ 0.1% average relative abundance and detected in all processes. The microbial community analysis assigned 106 families as the shared microbial constituents in the WWTPs. Correlation analysis showed that 98 of the 106 shared families were significantly correlated with total carbon (TC) and/or total nitrogen (TN) concentrations, suggesting that they may contribute to wastewater remediation. Most possible predatory or parasitic bacteria belonging to the phyla Bdellovibrionota, Myxococcota, and Candidatus Patescibacteria were found to be the shared families and negatively correlated with TC/TN; thus, they were frequently present in the WWTPs and could be involved in the removal of carbon/nitrogen derived from cell components. Shotgun metagenome-resolved metabolic reconstructions indicated that gene homologs associated with predation or parasitism are conserved in the Bdellovibrionota, Myxococcota, and Ca. Patescibacteria genomes (e.g., host interaction (hit) locus, Tad-like secretion complexes, and type IV pilus assembly proteins). This study provides insights into the complex microbial interactions potentially linked to the reduction of excess sludge biomass in these processes.